Análisis De Programas De Promoción De La Salud En Jóvenes Basados En Evidencia Desde El PYD - Alejandro, González-González; Elisa, Ortega Esteve Rosa; Fernanda, Hernández Martínez María; Cristina, Hinojosa Rodríguez Tiare; Lizbeth, Zablah Soberón Jessica; Diana, Betancourt Ocampo (European Scientific Journal, ESJ, 2018)
Objective: Analyze health promotion programs based on the perspective of Positive Youth Development (PYD) to identify characteristics, advantages and limitations in order to promote health and prevent substance use. Method and procedure: Bibliographic research was used, analyzing 37 intervention programs, specifically focused on the area of substance abuse. Results: The main categories analyzed relate to the objective of preventing the consumption and / or abuse of substances, an average duration of 15 sessions, working with adolescent population, taught by teachers and parents previously trained, using questionnaires, interviews and scales as evaluation methods, based on an experimental and quasi-experimental design, within family, school and community context components, resulting in the prevention of substance use, better school performance and the development of lifetime skills. Conclusions: This type of analysis allows us to identify, guide and organize the information obtained from each program that uses the PYD model and that has been analyzed in detail, with the purpose of contributing to the development of a program to promote healthy development in the Mexican population.